2017
DOI: 10.1021/acs.jmedchem.7b00210
|View full text |Cite
|
Sign up to set email alerts
|

Indazole-6-phenylcyclopropylcarboxylic Acids as Selective GPR120 Agonists with in Vivo Efficacy

Abstract: GPR120 agonists have therapeutic potential for the treatment of diabetes, but few selective agonists have been reported. We identified an indazole-6-phenylcyclopropylcarboxylic acid series of GPR120 agonists and conducted SAR studies to optimize GPR120 potency. Furthermore, we identified a (S,S)-cyclopropylcarboxylic acid structural motif which gave selectivity against GPR40. Good oral exposure was obtained with some compounds displaying unexpected high CNS penetration. Increased MDCK efflux was utilized to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…The ethanoic acid chain proved to be inactive, while 3- and 4-carbon chains with an unsubstituted N-aryl moiety were tolerated (EC 50 = 0.64–0.26 μM) but showed a low selectivity (hGPR120 calcium flux in CHO cell line). 121 For these reasons, a cyclopropyl carboxylic acid function was inserted, and the stereochemistry effect was analyzed, highlighting the activity of only the S,S -enantiomer (EC 50 = 0.69 μM vs >17 μM). One of the best two selective compounds was generated from the combination of two pyridine rings and a 3-F substituent on the phenyl at position 6 of the condensed-pyrazole bicyclic nucleus ( 28 , Figure 6 ).…”
Section: Gpr120 Agonists In T2dm Drug Discoverymentioning
confidence: 99%
“…The ethanoic acid chain proved to be inactive, while 3- and 4-carbon chains with an unsubstituted N-aryl moiety were tolerated (EC 50 = 0.64–0.26 μM) but showed a low selectivity (hGPR120 calcium flux in CHO cell line). 121 For these reasons, a cyclopropyl carboxylic acid function was inserted, and the stereochemistry effect was analyzed, highlighting the activity of only the S,S -enantiomer (EC 50 = 0.69 μM vs >17 μM). One of the best two selective compounds was generated from the combination of two pyridine rings and a 3-F substituent on the phenyl at position 6 of the condensed-pyrazole bicyclic nucleus ( 28 , Figure 6 ).…”
Section: Gpr120 Agonists In T2dm Drug Discoverymentioning
confidence: 99%
“…McCoull et al [ 93 ] identified an indazole-6-phenylcyclopropylcarboxylic acid series of GPR120 agonists and (S,S)-cyclopropylcarboxylic acid series of GPR40 agonists. Among them, compounds 160 and 161 exhibited potent GPR120 inhibition activity with EC 50 values of 0.74 and 0.36 μM, respectively ( Figure 46 ).…”
Section: Biological Applications Of Indazole Derivativesmentioning
confidence: 99%
“…[6] However, only a few articles about the osteogenic and adipogenic differentiation mediated by FFA4 have been reported. [7] There are many FFA4 agonists reported in the literature (Figure 1), [8][9][10][11] and there is no selective FFA4 agonists have reached clinical trial. [12] As the first highly selective non-carboxylic FFA4 agonist, many studies on GSK-137647A have been reported.…”
Section: Introductionmentioning
confidence: 99%